KETIDAKPASTIAN LINGKUNGAN DAN KINERJA MANAJERIAL : PERAN MEDIASI SISTEM AKUNTANSI MANAJEMEN - Izmi Dwira Eriani; Zaenal Fanani (Universitas Muhammadiyah Malang, 2019)
This study aims to test mediating management accounting system in the relationship of the environmental uncertainty on managerial performance. This research processed primary data obtained using a questionnaire distributed to managers of business unit of companies in the industrial area of PT. Surabaya Industrial Estate Rungkut. The sample analyzed were 216 questionnaire, using the Slovin formula. The analytical tool used is Structural Equation Modeling with the Partial Least Square approach. The result showed that management accounting systems mediated the effect of environmental uncertainty on managerial performance.